Polarization film and polarization plate
The polarizing film, featuring a polyvinyl alcohol-based resin film with an iodine treatment layer, addresses durability issues in high temperature and high humidity environments by enhancing absorbance and polarization performance.
Patent Information
- Application Number
- JP2025014480
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-01-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polarizing films face durability issues in high temperature and high humidity environments, leading to a decline in polarization performance.
A polarizing film made of a polyvinyl alcohol-based resin film containing iodine, with a treatment layer formed using a coating film containing a polyvinyl alcohol-based resin having a pH of 3.0 or less, which enhances durability and polarization performance.
The polarizing film demonstrates improved durability and polarization performance in high temperature and high humidity environments, as evidenced by increased absorbance after a 240-hour durability test.
Smart Images

Figure 2025061992000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing film and a polarizing plate. [Background technology]
[0002] In a liquid crystal display device, which is a representative image display device, a polarizing film is arranged on both sides of a liquid crystal cell due to its image formation method. As a method for producing a polarizing film, for example, a method has been proposed in which a laminate having a resin substrate and a polyvinyl alcohol (PVA)-based resin layer is stretched and then dyed to obtain a polarizing film on the resin substrate (for example, Patent Document 1). Since such a method can obtain a thin polarizing film, it has attracted attention as a possible contribution to the thinning of image display devices in recent years. However, there is a demand for further improvement in durability of thin polarizing films under high temperature and high humidity environments. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2001-343521 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made to solve the above-mentioned problems in the conventional art, and a main object of the present invention is to provide a polarizing film and a polarizing plate that are excellent in durability under high-temperature and high-humidity environments, and a method for producing such a polarizing film. [Means for solving the problem]
[0005] The polarizing film according to the embodiment of the present invention is made of a polyvinyl alcohol-based resin film containing iodine, and has a treatment layer formed on the surface thereof. The treatment layer is a solidified layer of a coating film of a treatment liquid containing a polyvinyl alcohol-based resin and having a pH of 3.0 or less. This polarizing film has an absorbance Abs of 100 nm at a wavelength of 600 nm after a durability test of 240 hours at a temperature of 60° C. and a relative humidity of 95%. 240 satisfies the following relationship with respect to the absorbance Abs0 before the durability test. 1.05≦Abs 240 / Abs0≦1.44 In one embodiment, the treatment layer has a thickness of 0.2 μm to 1.7 μm. In one embodiment, the polarizing film has a single transmittance of 43.0% or more. In one embodiment, the polarizing film has a thickness of 8 μm or less. According to another aspect of the present invention, there is provided a polarizing plate comprising the above polarizing film and a protective layer disposed on at least one side of the polarizing film. Effect of the Invention
[0006] According to the present invention, a polarizing film having excellent durability in a high-temperature and high-humidity environment can be obtained by contacting the polarizing film with a treatment liquid having a pH of 3.0 or less. Specifically, the polarizing film according to the embodiment of the present invention has an absorbance Abs of 100 nm at a wavelength of 600 nm after a durability test at a temperature of 60° C. and a relative humidity of 95% for 240 hours. 240 satisfies the following relationship with respect to the absorbance Abs0 before the durability test: Abs 240 / Abs0>1.00 That is, the polarizing film according to the embodiment of the present invention has an increased absorbance at a wavelength of 600 nm after a heat and humidity durability test. This means that the polarizing performance of the polarizing film according to the embodiment of the present invention can be improved in a high-temperature and high-humidity environment. Although the polarizing performance of a polarizing film is usually expected to decrease in a high-temperature and high-humidity environment, the improvement in durability of the polarizing film according to the embodiment of the present invention in a high-temperature and high-humidity environment is unexpectedly excellent. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a drying shrinkage treatment using a heating roll. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0009] A. Polarizing film The polarizing film according to the embodiment of the present invention is made of a polyvinyl alcohol (PVA)-based resin film containing iodine, and has an absorbance Abs at a wavelength of 600 nm after a durability test for 240 hours at a temperature of 60° C. and a relative humidity of 95%. 240 satisfies the following relationship with respect to the absorbance Abs0 before the durability test. Abs 240 / Abs0>1.00 This is because in the polarizing film according to the embodiment of the present invention, PVA-I5 has absorption around 600 nm. - This shows that the complex is not destroyed even in a heat and humidity durability test, but rather can grow. - The complex is destroyed in a high-temperature, high-humidity environment, and the polarizing performance of the polarizing film is expected to decrease in a high-temperature, high-humidity environment. However, the excellent durability of the polarizing film according to the embodiment of the present invention is unexpected and excellent. Although it is not theoretically clear, such excellent durability can be achieved by contacting the polarizing film with a treatment solution having a pH of 3.0 or less. 240 / Abs0 is preferably 1.05 or more, more preferably 1.10 or more, even more preferably 1.15 or more, particularly preferably 1.20 or more, and particularly preferably 1.25 or more. 240 The upper limit of / Abs0 may be, for example, 2.00. The absorbance is typically orthogonal absorbance. The orthogonal absorbance is calculated by the following formula based on the orthogonal transmittance Tc measured when calculating the degree of polarization described later. Orthogonal absorbance = log10(100 / Tc) The absorbance Abs0 before the durability test is the absorbance of the polarizing film in a normal state, and the Abs0 of the polarizing film at a wavelength of 600 nm is, for example, less than 5.0, preferably 4.3 or less, and more preferably 4.0 or less. The lower limit of Abs0 can be, for example, 2.0.
[0010] The thickness of the polarizing film is preferably 8 μm or less, more preferably 7 μm or less, further preferably 5 μm or less, and particularly preferably 3 μm or less. The lower limit of the thickness of the polarizing film may be 1 μm in one embodiment, and 2 μm in another embodiment. As described later, such a thickness can be realized by producing a polarizing film using, for example, a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. When the polarizing film is produced from a single resin film, the thickness of the polarizing film can be, for example, 12 μm to 35 μm.
[0011] The polarizing film preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizing film is preferably 42.0% or more, more preferably 42.5% or more, even more preferably 43.0% or more, particularly preferably 43.5% or more, and particularly preferably 44.0% or more. On the other hand, the single transmittance is preferably 47.0% or less, more preferably 46.0% or less. The polarization degree of the polarizing film is preferably 99.95% or more, more preferably 99.99% or more. On the other hand, the polarization degree is preferably 99.998% or less. According to the embodiment of the present invention, it is possible to achieve both a high single transmittance and a high polarization degree, and to realize excellent durability in a high temperature and high humidity environment as described above. The single transmittance is typically a Y value measured using an ultraviolet-visible spectrophotometer and corrected for luminosity. The single transmittance is a value when the refractive index of one surface of the polarizing plate is converted to 1.50 and the refractive index of the other surface is converted to 1.53. The polarization degree is typically calculated by the following formula based on the parallel transmittance Tp and the crossed transmittance Tc measured using an ultraviolet-visible spectrophotometer and corrected for luminous efficiency. Degree of polarization (%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0012] In one embodiment, the transmittance (single transmittance) of a thin polarizing film of 8 μm or less is typically measured using an ultraviolet-visible spectrophotometer with a laminate of a polarizing film (refractive index of surface: 1.53) and a protective layer (protective film) (refractive index: 1.50) as the measurement target. Depending on the refractive index of the surface of the polarizing film and / or the refractive index of the surface in contact with the air interface of the protective layer, the reflectance at the interface of each layer may change, and as a result, the measured transmittance may change. Therefore, for example, when a protective layer with a refractive index other than 1.50 is used, the measured transmittance may be corrected depending on the refractive index of the surface in contact with the air interface of the protective layer. Specifically, the corrected value C of the transmittance is expressed by the following formula using the reflectance R1 (transmission axis reflectance) of polarized light parallel to the transmission axis at the interface between the protective layer and the air layer. C=R1-R0 R0 = ((1.50-1) 2 / (1.50+1) 2 )×(T1 / 100) R1 = ((n1-1) 2 / (n1+1) 2 )×(T1 / 100) Here, R0 is the transmission axis reflectance when a protective layer with a refractive index of 1.50 is used, n1 is the refractive index of the protective layer used, and T1 is the transmittance of the polarizing film. For example, when a base material with a surface refractive index of 1.53 (such as a cycloolefin film or a film with a hard coat layer) is used as a protective layer, the correction amount C is about 0.2%. In this case, by adding 0.2% to the transmittance obtained by measurement, it is possible to convert a polarizing film with a surface refractive index of 1.53 into the transmittance when a protective layer with a refractive index of 1.50 is used. According to the calculation based on the above formula, when the transmittance T1 of the polarizing film is changed by 2%, the change in the correction value C is 0.03% or less, and the influence of the transmittance of the polarizing film on the value of the correction value C is limited. In addition, when the protective layer has absorption other than surface reflection, an appropriate correction can be made according to the amount of absorption.
[0013] The polarizing film may be produced using a single resin film, or may be produced using a laminate of two or more layers. A specific example of a polarizing film obtained using a laminate is a polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. A polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced, for example, by coating a PVA-based resin solution on the resin substrate, drying the resin substrate to form a PVA-based resin layer on the resin substrate, thereby obtaining a laminate of the resin substrate and the PVA-based resin layer, and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizing film. In an embodiment of the present invention, the polarizing film is brought into contact with a treatment liquid having a pH of 3.0 or less. This makes it possible to realize excellent durability in a high-temperature and high-humidity environment as described above. Preferably, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution and stretching it. Furthermore, the stretching may further include air-stretching the laminate at a high temperature (for example, 95°C or higher) before stretching in the boric acid aqueous solution, as necessary. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being conveyed in the longitudinal direction, thereby shrinking the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, it is possible to increase the crystallinity of PVA even when PVA is applied onto a thermoplastic resin, and it is possible to achieve high optical properties. At the same time, by increasing the orientation of PVA in advance, problems such as a decrease in the orientation or dissolution of PVA can be prevented when the PVA is immersed in water in the subsequent dyeing step or stretching step, and it is possible to achieve high optical properties. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disturbance of the orientation of polyvinyl alcohol molecules and the decrease in orientation can be suppressed compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of the polarizing film obtained through treatment steps in which the laminate is immersed in a liquid, such as dyeing treatment and underwater stretching treatment.Furthermore, the optical properties can be improved by shrinking the laminate in the width direction by drying shrinkage treatment. The obtained laminate of resin substrate / polarizing film may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizing film), or the resin substrate may be peeled off from the laminate of resin substrate / polarizing film, and any suitable protective layer may be laminated on the peeled surface depending on the purpose. Details of the method for producing the polarizing film will be described later in Section C.
[0014] B. Polarizing plate 1 is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention. The polarizing plate 100 has a polarizing film 10, a first protective layer 20 arranged on one side of the polarizing film 10, and a second protective layer 30 arranged on the other side of the polarizing film 10. The polarizing film 10 is the polarizing film of the present invention described in the above section A. One of the first protective layer 20 and the second protective layer 30 may be omitted. As described above, one of the first protective layer and the second protective layer may be a resin substrate used in the manufacture of the above polarizing film.
[0015] The first and second protective layers are formed of any suitable film that can be used as a protective layer for a polarizing film. Specific examples of materials that are the main components of the films include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates. Other examples include thermosetting resins or ultraviolet-curing resins such as (meth)acrylics, urethanes, (meth)acrylic urethanes, epoxys, and silicones. Other examples include glassy polymers such as siloxane polymers. Polymer films described in JP 2001-343529 A (WO01 / 37007) can also be used. The material for this film may be, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain, and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain, such as a resin composition containing an alternating copolymer of isobutene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. The polymer film may be, for example, an extrusion molded product of the above resin composition.
[0016] When the polarizing plate 100 is applied to an image display device, the thickness of the protective layer (outer protective layer) disposed on the opposite side to the display panel is typically 300 μm or less, preferably 100 μm or less, more preferably 5 μm to 80 μm, and further preferably 10 μm to 60 μm. When a surface treatment is applied, the thickness of the outer protective layer includes the thickness of the surface treatment layer.
[0017] When the polarizing plate 100 is applied to an image display device, the thickness of the protective layer (inner protective layer) disposed on the display panel side is preferably 5 μm to 200 μm, more preferably 10 μm to 100 μm, and even more preferably 10 μm to 60 μm. In one embodiment, the inner protective layer is a retardation layer having any appropriate retardation value. In this case, the in-plane retardation Re(550) of the retardation layer is, for example, 110 nm to 150 nm. "Re(550)" is the in-plane retardation measured with light having a wavelength of 550 nm at 23°C, and is calculated by the formula: Re=(nx-ny)×d. Here, "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), "nz" is the refractive index in the thickness direction, and "d" is the thickness (nm) of the layer (film).
[0018] C. Manufacturing method of polarizing film A method for producing a polarizing film according to one embodiment of the present invention includes: applying a PVA-based resin solution to one side of a long thermoplastic resin substrate and drying it to form a PVA-based resin layer to produce a laminate; stretching and dyeing the laminate to produce a polarizing film from the PVA-based resin layer; and contacting the polarizing film with a treatment liquid having a pH of 3.0 or less. By contacting the polarizing film with a treatment liquid having a pH of 3.0 or less, a polarizing film having excellent durability in a high-temperature and high-humidity environment can be realized. Preferably, the PVA-based resin solution further contains a halide. Preferably, the production method includes subjecting the laminate to an auxiliary air-stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction, in this order. The content of the halide in the PVA-based resin solution (as a result, the PVA-based resin layer) is preferably 5 to 20 parts by weight per 100 parts by weight of the PVA-based resin. The drying shrinkage treatment is preferably carried out using a heating roll, and the temperature of the heating roll is preferably 60°C to 120°C. The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment is preferably 2% or more. According to such a production method, the polarizing film described in the above item A can be obtained. In particular, a laminate including a PVA-based resin layer containing a halide is produced, the laminate is stretched by multi-stage stretching including auxiliary air stretching and underwater stretching, and the laminate after stretching is heated by a heating roll, whereby a polarizing film having excellent optical properties (typically, single transmittance and unit absorbance) can be obtained.
[0019] C-1. Preparation of laminate Any suitable method can be adopted as a method for producing a laminate of a thermoplastic resin substrate and a PVA-based resin layer. Preferably, a coating liquid containing a halide and a PVA-based resin is applied to the surface of the thermoplastic resin substrate, and then dried to form a PVA-based resin layer on the thermoplastic resin substrate. As described above, the content of the halide in the PVA-based resin layer is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA-based resin.
[0020] Any appropriate method can be used as the coating method of the coating liquid. For example, roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, knife coating (comma coating, etc.), etc. are listed. The coating and drying temperature of the coating liquid is preferably 50° C. or higher.
[0021] The thickness of the PVA-based resin layer is preferably 3 μm to 40 μm, and more preferably 3 μm to 20 μm.
[0022] Before forming the PVA-based resin layer, the thermoplastic resin substrate may be subjected to a surface treatment (e.g., corona treatment, etc.), or an easy-adhesion layer may be formed on the thermoplastic resin substrate. By carrying out such treatment, the adhesion between the thermoplastic resin substrate and the PVA-based resin layer can be improved.
[0023] C-1-1. Thermoplastic resin base material Any suitable thermoplastic resin film may be used as the thermoplastic resin substrate. Details of the thermoplastic resin substrate are described in, for example, JP 2012-73580 A. The entire disclosure of this publication is incorporated herein by reference.
[0024] C-1-2. Coating solution The coating liquid contains a halide and a PVA resin as described above. The coating liquid is typically a solution in which the halide and the PVA resin are dissolved in a solvent. Examples of the solvent include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine. These can be used alone or in combination of two or more. Among these, water is preferred. The concentration of the PVA resin in the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that is in close contact with the thermoplastic resin substrate can be formed. The content of the halide in the coating liquid is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA resin.
[0025] Additives may be added to the coating liquid. Examples of additives include plasticizers and surfactants. Examples of plasticizers include polyhydric alcohols such as ethylene glycol and glycerin. Examples of surfactants include nonionic surfactants. These can be used to further improve the uniformity, dyeability, and stretchability of the resulting PVA-based resin layer.
[0026] Any suitable resin can be used as the PVA resin. Examples include polyvinyl alcohol and ethylene-vinyl alcohol copolymer. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer is obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of the PVA resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree can be determined in accordance with JIS K 6726-1994. By using a PVA resin with such a saponification degree, a polarizing film with excellent durability can be obtained. If the saponification degree is too high, gelation may occur.
[0027] The average degree of polymerization of the PVA resin can be appropriately selected depending on the purpose. The average degree of polymerization is usually 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average degree of polymerization can be determined in accordance with JIS K 6726-1994.
[0028] Any suitable halide may be used as the halide. For example, iodide and sodium chloride may be used. For example, iodide may be potassium iodide, sodium iodide, and lithium iodide. Among these, potassium iodide is preferred.
[0029] The amount of the halide in the coating solution is preferably 5 to 20 parts by weight per 100 parts by weight of the PVA-based resin, and more preferably 10 to 15 parts by weight per 100 parts by weight of the PVA-based resin. If the amount of the halide exceeds 20 parts by weight per 100 parts by weight of the PVA-based resin, the halide may bleed out, causing the final polarizing film to become cloudy.
[0030] Generally, the orientation of polyvinyl alcohol molecules in the PVA-based resin increases when the PVA-based resin layer is stretched, but when the stretched PVA-based resin layer is immersed in a liquid containing water, the orientation of the polyvinyl alcohol molecules may become disordered, and the orientation may decrease. In particular, when a laminate of a thermoplastic resin and a PVA-based resin layer is stretched in boric acid water, the tendency of the orientation degree to decrease is remarkable when the laminate is stretched in boric acid water at a relatively high temperature to stabilize the stretching of the thermoplastic resin. For example, the stretching of a PVA film alone in boric acid water is generally performed at 60°C, whereas the stretching of a laminate of A-PET (thermoplastic resin substrate) and a PVA-based resin layer is performed at a high temperature of about 70°C, and in this case, the orientation of PVA at the initial stage of stretching may decrease before it increases due to underwater stretching. In response to this, a laminate of a PVA-based resin layer containing a halide and a thermoplastic resin substrate is prepared, and the laminate is stretched at high temperature (auxiliary stretching) in air before being stretched in boric acid water, so that the crystallization of the PVA-based resin in the PVA-based resin layer of the laminate after the auxiliary stretching can be promoted. As a result, when the PVA-based resin layer is immersed in a liquid, the orientation of the polyvinyl alcohol molecules is disturbed and the orientation is reduced, compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of the polarizing film obtained through a process in which the laminate is immersed in a liquid, such as a dyeing process and an underwater stretching process.
[0031] C-2. Aerial supplementary stretching process In particular, in order to obtain high optical properties, a two-stage stretching method is selected, which combines dry stretching (auxiliary stretching) and stretching in boric acid water. By introducing auxiliary stretching like two-stage stretching, it is possible to stretch while suppressing the crystallization of the thermoplastic resin substrate, which solves the problem of the thermoplastic resin substrate being excessively crystallized and reduced in stretchability in the subsequent stretching in boric acid water, and the laminate can be stretched at a higher magnification. Furthermore, when applying a PVA-based resin onto a thermoplastic resin substrate, in order to suppress the influence of the glass transition temperature of the thermoplastic resin substrate, it is necessary to lower the application temperature compared to when applying a PVA-based resin onto a normal metal drum, which may result in a problem that the crystallization of the PVA-based resin is relatively low and sufficient optical properties cannot be obtained. In contrast, by introducing auxiliary stretching, it is possible to increase the crystallinity of the PVA-based resin even when applying a PVA-based resin onto a thermoplastic resin, and it is possible to achieve high optical properties. At the same time, by increasing the orientation of the PVA-based resin in advance, problems such as a decrease in the orientation of the PVA-based resin or dissolution when the resin is immersed in water in the subsequent dyeing and stretching processes can be prevented, making it possible to achieve high optical properties.
[0032] The stretching method of the auxiliary air stretching may be fixed end stretching (for example, a method of stretching using a tenter stretching machine) or free end stretching (for example, a method of uniaxially stretching a laminate between rolls with different peripheral speeds), but in order to obtain high optical properties, free end stretching may be actively adopted. In one embodiment, the air stretching process includes a heated roll stretching process in which the laminate is stretched by the difference in peripheral speed between heated rolls while being transported in its longitudinal direction. The air stretching process typically includes a zone stretching process and a heated roll stretching process. The order of the zone stretching process and the heated roll stretching process is not limited, and the zone stretching process may be performed first, or the heated roll stretching process may be performed first. The zone stretching process may be omitted. In one embodiment, the zone stretching process and the heated roll stretching process are performed in this order. In another embodiment, the film is stretched by gripping the film end in a tenter stretching machine and widening the distance between the tenters in the flow direction (the widening of the distance between the tenters is the stretching ratio). At this time, the distance of the tenter in the width direction (perpendicular to the machine direction) is set to be as close as possible. Preferably, it can be set to be as close as possible to the free end stretching ratio in the machine direction. In the case of free end stretching, the shrinkage ratio in the width direction = (1 / stretching ratio) 1 / 2 It is calculated as follows.
[0033] The auxiliary air-drawing may be performed in one step or in multiple steps. When the auxiliary air-drawing is performed in multiple steps, the draw ratio is the product of the draw ratios in each step. The draw direction in the auxiliary air-drawing is preferably approximately the same as the draw direction in the underwater drawing.
[0034] The stretching ratio in the auxiliary air-stretching is preferably 2.0 to 3.5 times. The maximum stretching ratio in the case of combining the auxiliary air-stretching and the underwater stretching is preferably 5.0 times or more, more preferably 5.5 times or more, and even more preferably 6.0 times or more, based on the original length of the laminate. In this specification, the "maximum stretching ratio" refers to the stretching ratio just before the laminate breaks, and refers to a value 0.2 lower than the stretching ratio at which the laminate breaks, which is determined separately.
[0035] The stretching temperature of the auxiliary in-air stretching can be set to any appropriate value depending on the material of the thermoplastic resin substrate, the stretching method, etc. The stretching temperature is preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably equal to or higher than the glass transition temperature (Tg) of the thermoplastic resin substrate + 10°C, and particularly preferably equal to or higher than Tg + 15°C. On the other hand, the upper limit of the stretching temperature is preferably 170°C. By stretching at such a temperature, rapid crystallization of the PVA resin can be suppressed, and defects due to the crystallization (for example, the orientation of the PVA resin layer due to stretching is hindered) can be suppressed.
[0036] C-3. Insolubilization, dyeing and crosslinking treatments If necessary, after the auxiliary air stretching treatment, an insolubilization treatment is performed before the underwater stretching treatment or the dyeing treatment. The insolubilization treatment is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. The dyeing treatment is typically performed by dyeing the PVA-based resin layer with a dichroic substance (typically iodine). If necessary, after the dyeing treatment, a crosslinking treatment is performed before the underwater stretching treatment. The crosslinking treatment is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. Details of the insolubilization treatment, the dyeing treatment, and the crosslinking treatment are described, for example, in JP 2012-73580 A (above).
[0037] C-4. Underwater stretching process The underwater stretching treatment is performed by immersing the laminate in a stretching bath. The underwater stretching treatment allows stretching at a temperature lower than the glass transition temperature (typically about 80° C.) of the thermoplastic resin substrate or the PVA-based resin layer, and allows the PVA-based resin layer to be stretched at a high magnification while suppressing crystallization. As a result, a polarizing film having excellent optical properties can be produced.
[0038] The stretching method of the laminate can be any appropriate method. Specifically, it may be fixed end stretching or free end stretching (for example, a method of uniaxially stretching the laminate by passing it between rolls having different peripheral speeds). Preferably, free end stretching is selected. The stretching of the laminate may be performed in one stage or multiple stages. When performing the stretching in multiple stages, the stretching ratio (maximum stretching ratio) of the laminate described below is the product of the stretching ratios in each stage.
[0039] The underwater stretching is preferably performed by immersing the laminate in an aqueous solution of boric acid (stretching in boric acid water). By using an aqueous solution of boric acid as a stretching bath, it is possible to impart to the PVA-based resin layer rigidity that can withstand the tension applied during stretching and water resistance that does not dissolve in water. Specifically, boric acid can generate tetrahydroxyborate anions in the aqueous solution and crosslink with the PVA-based resin through hydrogen bonds. As a result, it is possible to impart rigidity and water resistance to the PVA-based resin layer and stretch it well, and a polarizing film having excellent optical properties can be produced.
[0040] The boric acid aqueous solution is preferably obtained by dissolving boric acid and / or a borate in water as a solvent. The boric acid concentration is preferably 1 to 10 parts by weight, more preferably 2.5 to 6 parts by weight, and particularly preferably 3 to 5 parts by weight, relative to 100 parts by weight of water. By setting the boric acid concentration to 1 part by weight or more, dissolution of the PVA-based resin layer can be effectively suppressed, and a polarizing film with higher characteristics can be produced. In addition to boric acid or a borate, an aqueous solution obtained by dissolving a boron compound such as borax, glyoxal, glutaraldehyde, or the like in a solvent can also be used.
[0041] Preferably, an iodide is added to the stretching bath (boric acid aqueous solution). By adding an iodide, it is possible to suppress the elution of iodine adsorbed in the PVA resin layer. Specific examples of the iodide are as described above. The concentration of the iodide is preferably 0.05 to 15 parts by weight, more preferably 0.5 to 8 parts by weight, relative to 100 parts by weight of water.
[0042] The stretching temperature (liquid temperature of the stretching bath) is preferably 40°C to 85°C, more preferably 60°C to 75°C. At such a temperature, the laminate can be stretched at a high ratio while suppressing dissolution of the PVA-based resin layer. Specifically, as described above, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 60°C or higher in relation to the formation of the PVA-based resin layer. In this case, if the stretching temperature is lower than 40°C, there is a risk that the substrate cannot be stretched well even when the plasticization of the thermoplastic resin substrate by water is taken into consideration. On the other hand, the higher the temperature of the stretching bath, the higher the solubility of the PVA-based resin layer, and there is a risk that excellent optical properties cannot be obtained. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.
[0043] The stretching ratio in the underwater stretching is preferably 1.5 times or more, more preferably 3.0 times or more. The total stretching ratio of the laminate is preferably 5.0 times or more, more preferably 5.5 times or more, based on the original length of the laminate. By achieving such a high stretching ratio, a polarizing film with extremely excellent optical properties can be produced. Such a high stretching ratio can be achieved by employing an underwater stretching method (stretching in boric acid water).
[0044] C-5. Drying shrinkage treatment The drying shrinkage treatment may be performed by zone heating, which heats the entire zone, or by heating the transport roll (using a so-called heating roll) (heat roll drying method). Preferably, both are used. By drying using a heating roll, it is possible to efficiently suppress the heat curl of the laminate and produce a polarizing film with excellent appearance. Specifically, by drying the laminate in a state where it is aligned with the heating roll, it is possible to efficiently promote the crystallization of the thermoplastic resin substrate and increase the crystallinity, and even at a relatively low drying temperature, it is possible to satisfactorily increase the crystallinity of the thermoplastic resin substrate. As a result, the rigidity of the thermoplastic resin substrate increases and it becomes in a state where it can withstand the shrinkage of the PVA-based resin layer due to drying, and curling is suppressed. In addition, by using a heating roll, it is possible to dry the laminate while maintaining it in a flat state, so that it is possible to suppress not only curling but also wrinkles. At this time, the optical properties of the laminate can be improved by shrinking it in the width direction by the drying shrinkage treatment. This is because the orientation of the PVA and the PVA / iodine complex can be effectively increased. The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment is preferably 1% to 10%, more preferably 2% to 8%, and particularly preferably 4% to 6%.
[0045] 2 is a schematic diagram showing an example of the drying shrinkage treatment. In the drying shrinkage treatment, the laminate 200 is dried while being transported by transport rolls R1 to R6 heated to a predetermined temperature and guide rolls G1 to G4. In the illustrated example, the transport rolls R1 to R6 are arranged so as to alternately and continuously heat the surface of the PVA resin layer and the surface of the thermoplastic resin substrate, but, for example, the transport rolls R1 to R6 may be arranged so as to continuously heat only one surface of the laminate 200 (for example, the thermoplastic resin substrate surface).
[0046] Drying conditions can be controlled by adjusting the heating temperature of the transport rolls (temperature of the heating rolls), the number of heating rolls, the contact time with the heating rolls, etc. The temperature of the heating rolls is preferably 60°C to 120°C, more preferably 65°C to 100°C, and particularly preferably 70°C to 80°C. The crystallinity of the thermoplastic resin can be favorably increased, curling can be favorably suppressed, and an optical laminate with extremely excellent durability can be produced. The temperature of the heating rolls can be measured by a contact thermometer. In the illustrated example, six transport rolls are provided, but there is no particular restriction as long as there are multiple transport rolls. The number of transport rolls is usually 2 to 40, preferably 4 to 30. The contact time (total contact time) between the laminate and the heating rolls is preferably 1 to 300 seconds, more preferably 1 to 20 seconds, and even more preferably 1 to 10 seconds.
[0047] The heating roll may be provided in a heating furnace (for example, an oven) or in a normal production line (under room temperature environment). It is preferably provided in a heating furnace equipped with a blowing means. By using drying with a heating roll in combination with hot air drying, it is possible to suppress abrupt temperature changes between the heating rolls, and it is possible to easily control shrinkage in the width direction. The hot air drying temperature is preferably 30°C to 100°C. The hot air drying time is preferably 1 second to 300 seconds. The hot air speed is preferably about 10 m / s to 30 m / s. The wind speed is the wind speed in the heating furnace, and can be measured by a mini-vane type digital anemometer.
[0048] C-6. Contact with processing liquid As described above, a laminate of a thermoplastic resin substrate and a polarizing film can be obtained. In an embodiment of the present invention, the polarizing film is contacted with a treatment liquid having a pH of 3.0 or less. In one embodiment, the laminate can be directly contacted with the treatment liquid to bring the polarizing film into contact with the treatment liquid. In this case, typically, the thermoplastic resin substrate can be directly used as a protective layer for the polarizing film. Alternatively, a resin film (to be a protective layer) may be attached to the polarizing film surface of the laminate that has been contacted with the treatment liquid to prepare a laminate of protective layer / polarizing film / thermoplastic resin substrate, and the thermoplastic resin substrate may be peeled off from the laminate to prepare a polarizing plate having a configuration of protective layer / polarizing film. In another embodiment, a resin film (to be a protective layer) is attached to the polarizing film surface of the laminate to prepare a laminate of protective layer / polarizing film / thermoplastic resin substrate, and the thermoplastic resin substrate is peeled off from the laminate to prepare a laminate of protective layer / polarizing film (polarizing plate). The polarizing film can be contacted with the treatment liquid by contacting the obtained polarizing plate with the treatment liquid.
[0049] The polarizing film may be brought into contact with the treatment liquid by any suitable method. Representative examples include application of the treatment liquid to the polarizing film and immersion of the polarizing film (substantially, a laminate or a polarizing plate) in the treatment liquid. Any suitable method may be adopted as the application method. Specific examples include the method described in section C-1 as the application method of the coating liquid. Immersion may also be carried out by any suitable manner. For example, the treatment liquid may be added to the cleaning bath of the cleaning treatment, a bath of the treatment liquid may be used instead of the cleaning bath, or a bath of the treatment liquid may be provided separately from the cleaning bath. Note that the cleaning treatment is typically carried out after the underwater stretching treatment and before the drying shrinkage treatment. When a bath of the treatment liquid is provided separately, the bath of the treatment liquid may be provided between the cleaning bath and the drying shrinkage treatment equipment (i.e., contact with the treatment liquid may be carried out between the cleaning treatment and the drying shrinkage treatment), or may be provided downstream of the means for peeling off the thermoplastic resin substrate (i.e., contact with the treatment liquid may be carried out after the thermoplastic resin substrate is peeled off).
[0050] As the treatment liquid, any suitable acid liquid can be used as long as the pH is 3.0 or less. Specific examples of the treatment liquid include hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, and citric acid. The treatment liquid is preferably a strong acid aqueous solution. Specific examples of the strong acid include hydrochloric acid, sulfuric acid, and nitric acid. The lower the pH of the treatment liquid (the stronger the acidity), the more preferable it is. Specifically, the pH is preferably 2.7 or less, more preferably 2.5 or less, even more preferably 2.0 or less, and particularly preferably 1.5 or less.
[0051] The acid concentration of the treatment liquid is preferably 0.02% by weight to 3.0% by weight, more preferably 0.04% by weight to 2.0% by weight, and further preferably 0.1% by weight to 1.0% by weight.
[0052] The treatment liquid may contain a water-soluble resin (e.g., a PVA-based resin). The water-soluble resin can function as a binder. The concentration of the water-soluble resin in the treatment liquid is preferably 3% by weight to 5% by weight. In this case, a treatment layer can be formed by applying and drying the treatment liquid. By forming such a treatment layer, a polarizing film having the desired durability can be obtained. The thickness of the treatment layer is preferably 1.7 μm or less, and more preferably 0.2 μm to 1.4 μm.
[0053] After contact with the treatment liquid, drying may be carried out as necessary. The drying temperature is preferably 40°C to 90°C, more preferably 50°C to 70°C.
[0054] C-7. Variations Although the manufacturing method using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate has been described in sections C-1 to C-6, the present invention can also be applied to a manufacturing method using a single PVA-based resin film. Such a manufacturing method typically involves subjecting a long PVA-based resin film to swelling, dyeing, crosslinking and washing treatments while uniaxially stretching the film in the long direction with a roll stretching machine, and finally drying treatment. The contact with the treatment liquid can typically be performed by immersion in a washing bath containing the treatment liquid, immersion in a treatment bath after washing treatment, or application of the treatment liquid after washing treatment. EXAMPLES
[0055] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified. (1) Thickness The thickness was measured using an interference thickness meter (Otsuka Electronics Co., Ltd., product name "MCPD-3000"). (2) Single unit transmittance and orthogonal absorbance For the polarizing plates (protective layer / polarizing film) of the examples and comparative examples, the single transmittance Ts, parallel transmittance Tp, and crossed transmittance Tc measured using an ultraviolet-visible spectrophotometer (manufactured by Otsuka Electronics Co., Ltd., product name "LPF-200") were taken as Ts, Tp, and Tc of the polarizing film, respectively. These Ts, Tp, and Tc are Y values measured using a 2-degree visual field (C light source) according to JIS Z8701 and corrected for visibility. The refractive index of the protective film was 1.50, and the refractive index of the surface of the polarizing film opposite the protective film was 1.53. In addition, the orthogonal absorbance was calculated using the measured Tc at each wavelength according to the following formula. Orthogonal absorbance = log10(100 / Tc) The orthogonal absorbance Abs0 was calculated from the orthogonal transmittance Tc at a measurement wavelength of 600 nm using an "LPF-200" manufactured by Otsuka Electronics Co., Ltd. Note that it is possible to perform equivalent measurements of Abs0 using an "V-7100" manufactured by JASCO Corporation. The polarizing plate was then subjected to a durability test at a temperature of 60° C. and a relative humidity of 95% for 240 hours. 240 was determined in the same manner as above.
[0056] [Example 1] The thermoplastic resin substrate was a long, amorphous, isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) with a water absorption rate of 0.75% and a Tg of approximately 75°C. One side of the resin substrate was subjected to corona treatment (treatment conditions: 55 W min / m 2 ) was applied. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER Z410") in a ratio of 9:1. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 20 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched at its free end to 2.4 times its original size in the machine direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the final polarizing plate would be 45.0% (dyeing process). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4.0 wt %, potassium iodide 5 wt %) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds so that the total stretch ratio was 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water, pH=6) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, while drying in an oven maintained at 90°C, it was brought into contact with a SUS heated roll whose surface temperature was maintained at 75°C for about 2 seconds (drying shrinkage treatment). The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment was 2%. In this way, a polarizing film with a thickness of 5.0 μm was formed on the resin substrate, a cycloolefin film (manufactured by ZEON, product name "G-Film") was attached to the surface of the polarizing film as a protective layer (protective film) with a UV-curable adhesive (thickness 1.0 μm), and then the resin substrate was peeled off to obtain a laminate having a protective layer / polarizing film configuration. The single transmittance (Ts) of the obtained laminate was 45.0%, which was a value obtained by correcting the actual measured value by +0.2% and converting it to a state of 1.53 / 1.50 because the surface refractive index of the polarizing film / protective layer constituting the laminate was 1.53 / 1.53. Next, a treatment liquid (pH = 1.3) obtained by dissolving 0.3 wt% hydrochloric acid and 3.5 wt% PVA (JC-25) in water was applied to the polarizing film surface of the laminate to a thickness of 0.6 μm, and dried at 60°C for 4 minutes to form a treatment layer. In this manner, the polarizing plate of this example was obtained.
[0057] The obtained polarizing plate (effectively a polarizing film) was measured for its single transmittance and Abs 240 / Abs0 is shown in Table 1.
[0058] [Example 2] A polarizing plate was produced in the same manner as in Example 1, except that the concentration of the dye bath was adjusted to set the single transmittance (Ts) of the polarizing film to 44.0%. 240 / Abs0 is shown in Table 1.
[0059] [Examples 3 to 19] A polarizing plate was prepared by adjusting the single transmittance of the polarizing film, the contact method with the treatment liquid, the pH of the treatment liquid, the type of acid contained in the treatment liquid, and the thickness of the treatment layer as shown in Table 1. The single transmittance and Abs 240 / Abs0 is shown in Table 1.
[0060] [Example 20] A polarizing plate was produced in the same manner as in Example 2, except that the treatment solution did not contain a PVA resin (i.e., no treatment layer was formed) and the pH of the treatment solution was set to 0.9. The single transmittance and Abs 240 / Abs0 is shown in Table 1.
[0061] [Example 21] The laminate of thermoplastic resin substrate / PVA-based resin layer was subjected to the auxiliary air stretching treatment, insolubilization treatment, dyeing treatment, crosslinking treatment and underwater stretching treatment in the same manner as in Example 2. The laminate that had been stretched underwater was immersed in a treatment bath (pH=1.6) at a liquid temperature of 20°C (contact with the treatment liquid). The treatment bath was prepared by adding hydrochloric acid to a normal washing bath (aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water). Thereafter, while drying in an oven maintained at 90°C, the laminate was brought into contact with a SUS heated roll whose surface temperature was maintained at 75°C for approximately 2 seconds (drying shrinkage treatment). The shrinkage rate of the laminate in the width direction due to the drying shrinkage treatment was 2%. Next, a cycloolefin film (manufactured by ZEON, product name "G-Film") was attached to the surface of the polarizing film as a protective layer (protective film) using a UV-curable adhesive (thickness 1.0 μm), and then the resin substrate was peeled off to obtain a polarizing plate having a protective layer / polarizing film configuration. The obtained polarizing plate (effectively a polarizing film) was measured for its single transmittance and Abs 240 / Abs0 is shown in Table 1.
[0062] [Comparative Examples 1 to 2] Polarizing plates were prepared in the same manner as in Examples 1 and 2, except that no contact with the treatment liquid was performed. The single transmittance and Abs 240 / Abs0 is shown in Table 1.
[0063] [Comparative Example 3] A polarizing plate was produced in the same manner as in Comparative Example 1, except that the single transmittance of the polarizing film was 43.0%. 240 / Abs0 is shown in Table 1.
[0064] [Comparative Examples 4 to 9] The polarizing plate was prepared by adjusting the single transmittance of the polarizing film, the contact method with the treatment liquid, the pH of the treatment liquid, the type of acid contained in the treatment liquid, and the thickness of the treatment layer (if formed) as shown in Table 1. The single transmittance and Abs 240 / Abs0 is shown in Table 1.
[0065] [Example 22] A long roll of a 55 μm-thick PVA resin film (manufactured by Nippon Gosei Co., Ltd., product name "PS7500") was uniaxially stretched in the long direction by a roll stretching machine to a total stretch ratio of 6.0 times, while simultaneously undergoing swelling, dyeing, crosslinking and washing treatments, and finally drying treatment to produce a polarizing film with a thickness of 23 μm. After the washing treatment and before the drying treatment, the same treatment liquid as in Example 2 was applied to one side of the PVA resin film (polarizing film) in the same manner as in Example 2. The single transmittance and Abs 240 / Abs0 is shown in Table 1.
[0066] [Example 23] A polarizing film having a thickness of 23 μm was prepared in the same manner as in Example 22, except that the PVA resin film (polarizing film) was passed through a treatment bath similar to that in Example 21 instead of the cleaning bath for the cleaning treatment (therefore, no treatment liquid was applied after the cleaning treatment). 240 / Abs0 is shown in Table 1.
[0067] [Table 1]
[0068] As is clear from Table 1, the polarizing films of the examples of the present invention have an Abs 240 The polarizing films of Comparative Examples 1 to 3, which were not brought into contact with a treatment liquid, and the polarizing films of Comparative Examples 4 to 9, which were brought into contact with a treatment liquid having a pH of more than 3.0, all had an Abs 240 / Abs0 was less than 1.00. In addition, in Comparative Example 7 in which boric acid was used as the treatment liquid, the treatment liquid gelled, and contact itself was impossible. [Industrial Applicability]
[0069] The polarizing film and polarizing plate of the present invention are suitably used in liquid crystal displays. [Explanation of symbols]
[0070] 10 Polarizing film 20 First protective layer 30 Second layer of protection 100 Polarizing Plate
Claims
[Claim 1] It is made of a polyvinyl alcohol resin film containing iodine, A treatment layer is formed on the surface, the treated layer is a solidified layer of a coating film of a treatment liquid containing a polyvinyl alcohol-based resin and having a pH of 3.0 or less, Absorbance Abs at a wavelength of 600 nm after a 240-hour durability test at a temperature of 60°C and a relative humidity of 95% 240 is the absorbance Abs before the durability test 0 A polarizing film that satisfies the following relationship: 1.05≦Abs 240 / Abs 0 ≦1.44
Citation Information
Patent Citations
Polarizing plate and method for manufacturing the same
JP2001343521A